Expanding access to HIV testing through Canadian community pharmacies: findings from the APPROACH study - Deborah V. Kelly; Jason Kielly; Christine Hughes; Jacqueline Gahagan; Shabnam Asghari; Stephanie Hancock; Kimberley Burt; Petra Smyczek; Carmen Charlton; Hai Nguyen (BMC, 2020)
Abstract Background There is a need for acceptable and feasible HIV testing options to ensure people living with HIV know their status so they can access care. Pharmacist-provided HIV point-of-care testing (POCT) may overcome testing barriers, including privacy concerns, testing wait times, and improve accessibility. In the APPROACH study, we aimed to develop and assess an HIV POCT program in community pharmacies for future scale up and evaluation. This paper describes the program uptake, participant and pharmacist experiences, and implementation factors. Methods A pharmacist-provided HIV POCT program was offered in 4 pharmacies in two Canadian provinces. A mixed methods design incorporated self-report questionnaire data, participant telephone interviews, pharmacist focus groups, workload analysis, and situational analysis to assess the uptake, acceptability and feasibility of the HIV POCT program. Results Over the 6-month pilot, 123 HIV tests were performed. One new case of HIV was identified; this participant was linked with confirmatory testing and HIV care. Participants were predominantly male (76%), with a mean age of 35 years. This was the first HIV test for 27% participants, and 75% were at moderate to very high risk of undiagnosed HIV infection, by Denver HIV Risk Score. Questionnaires and telephone interviews showed participants were very satisfied with the program; 99% agreed HIV POCT should be routinely offered in pharmacies and 78% were willing to pay for the service. Participants felt the pharmacy was convenient, discreet, and that the pharmacist was supportive and provided education about how to reduce their future risk. Pharmacists felt prepared, confident, and expressed professional satisfaction with offering HIV POCT. Community and public health supports, clear linkage to care plans to refer participants with positive HIV POCT results, and provision of counselling tools were important enabling factors for the program. Pharmacist remuneration, integration with existing healthcare systems, and support for ongoing promotion of HIV POCT availability in pharmacies were identified as needs for future scale-up and sustainability. Conclusions A successful model of pharmacy-based POCT, including linkage to care, was developed. Further research is needed to determine the effectiveness and cost-effectiveness of this approach in finding new diagnoses and linking them with care. Trial registration Retrospectively registered with clinicaltrials.gov ( NCT03210701 ) on July 6, 2017.